Perception of mealybug wilt effect and management among pineapple farmers in west of Johor / Mohd Syazwan Syafiq Riduan - Riduan, Mohd Syazwan Syafiq (Faculty of Plantation and Agrotechnology, 2019)
Pineapple mealybug wilt-associated viruses (PMWaVs) have been associated with mealybug wilt of pineapple. The vulnerable of the disease threatened pineapple industry globally that able causes the damage on the crop up to 40% to 100%. In Malaysia, mealybug is the insect pest that almost commonly found in all pineapple growing area. However, the significant of viruses (PMWaVs) infection is still not recognized although the disease symptoms already shown in certain pineapple field because the studied of its damage and extend of incidence have not been investigated in this country. Hence, this study was conducted to determine the farmer’s knowledge and perception on the effect and management of mealybug wilt of pineapple in west of Johor. The structured questionnaires were distributed to 165 pineapple farmers in Pontian and Kluang of Johor. The data were analyzed by descriptive statistic and inferential statistic including percentage, mean, standard deviation, correlation and regression. Majority (39.4%) of the farmers having less than 5 years experiences in pineapple cultivation. From the result, it showed that the respondents did not have experienced dealing with mealybug wilt of pineapple in their farm and cannot identified the symptoms of disease. The respondents strongly agreed that the disease can be control by not used the parent materials that had been infected. Both knowledge (β= -.053) of disease and incidence and severity (β= -.086) were negative correlation toward control management while perception of mealybug wilt of pineapple (β=.005) was very weak correlation